Clinical, Imaging, and Endoscopic Profile of Patients with Abdominal Tuberculosis - Shafiq, Syed (Journal of Digestive Endoscopy, 2019)
Aims: The aim is to study the clinical, imaging, and endoscopic profile of patients with abdominal tuberculosis (TB) in a tertiary care center.Subjects and Methods: This was a prospective observational study conducted at Meenakshi Medical College Hospital, Kancheepuram, over a 3-year period, from March 2011 to February 2014. A total of 76 patients were diagnosed with abdominal TB based on their clinical, pathological, endoscopic, and radiological features. A meticulous history and physical examination with complete blood count, human immunodeficiency virus (HIV) status, chest X-ray, ultrasound abdomen, upper endoscopy, and colonoscopy was performed. Barium study, ascitic fluid analysis, and contrast-enhanced computed tomography of the abdomen and pelvis with peritoneal biopsies where need be were also obtained. All the patients received antituberculosis treatment (ATT) under close surveillance and monitoring.Results: The total number of patients enrolled in our study was 76 with age ranging from 18 to 75 years; 40 were male and 36 were female. There was a significant overlap of symptoms, and most of the patients presented with a multitude of complaints. Abdominal pain was the most common complaint noted in 70 patients, followed by loss of appetite and weight loss in 52, fever in 48, constipation in 28, abdominal distention in 14, and diarrhea in 6 patients. Two patients presented with acute intestinal obstruction requiring emergency surgical intervention. Fever was the most common finding followed by anemia, ascites, abdominal tenderness, and a palpable abdominal mass. A history of pulmonary Koch's was elicited in 28 patients, and 17 had defaulted on treatment. All the patients enrolled in our study received ATT although six were lost to follow-up.Conclusions: Abdominal TB can present with a myriad of signs and symptoms, and early diagnosis and treatment are the keys for an effective cure and for reducing the morbidity and mortality from this chronic granulomatous disease.
Keywords: abdominal tuberculosis; ascites; diagnostic laparotomy; loss of appetite